The comparison of two different direct acting antiviral regimens in treatment of chronic hepatitis C virus (Annals of Medical Research, 2021)
Aim: Chronic hepatitis C virus (HCV) is considered a critical threat to the public health in the world. We compared treatment outcomes of Ombitasvir, Paritaprevir and Ritonavir with Dasabuvir (PrOD) and Ledipasvir (LDV) and Sofosbuvir (SOF) in real world patients with chronic HCV in treatment-naïve and pre-treated patients with chronic HCV.MaterialS and Methods: 91 adult patients enrolled in our study and were divided in two groups. The first group; consisted of 53 patients, who orally received a fixed-dose combination tablet comprised of LDV and SOF once daily for 24 weeks. The second group; consisted of 38 patients, who orally received a fixed-dose combination tablet comprised of PrOD twice daily for 12 weeks without regard to fat or calorie content. Results: The results showed that sustained virologic response (SVR) rates were 100% in the both groups analyzed. 76 adverse events were occurred in total. 46 of overall adverse events were found on patients in the first group and 30 of those events were found on patients in the second group. Weakness (13.1%), pruritus (5.5%), myalgia (1.1%) nausea (5.5%), dry mouth (1.1%) and insomnia (1.1%) were observed among the patients. Twelve weeks after initiating treatment, virologic suppression was accomplished for all patients in the both groups. Additionally, laboratory analysis concluded that HCV-RNA levels of the overall patients were negative after 48 weeks of the onset of the treatment.Conclusion: The real world comparative analysis of two distinct treatment regimens concluded that administration of PrOD and LDV/SOF on the patients with chronic HCV has an extremely effective outcome. SVR12 rates of 100% were obtained in both treatment regimens for all treatment naïve and treatment-experienced patients regardless of cirrhosis occurrence and of HCV genotype.
Keywords: Chronic hepatitis C virus; direct acting antivirals; treatment